Dental caries on distal surface of mandibular second molars - Silva, Hudson Oliveira; Pinto, Antonione Santos Bezerra; Pinto, Moara e Silva Conceição; Rego, Marconi Raphael de Siqueira; Gois, Jamyra Ferreira; de Araujo, Thyago Leite Campos; Mendes, Jean De Pinho (Brazilian Dental Science, 2015)
Objective: The aim of the study was to evaluate the frequency of distal caries in the second molar influenced by the angulation of the third molar adjacent on panoramic radiographs in a clinical dental radiology. Material and Methods: A descriptive and quantitative study that examined 750 panoramic radiographs, of this total, 120 were in accordance with the inclusion criteria of the study was conducted. Results: 157 seconds and third molars analyzed the prevalence of caries in the distal of the second molar was 25.5%. The most prevalent angle position of the third molar was 57.3% with the vertical, but the position with the highest percentage of decayed molar second distal mesioangular was 50% of the cases. The elements listed, males obtained 40% of second molar distal caries versus 17% for females. People aged 35 or older had the highest incidence with 50% distal caries while other bands obtained 16.21% in the group 18-24 years, and 23.52% in 25-34 years. Conclusion: It was possible to establish a sliding scale on the indication for prophylactic removal of mandibular third molar according to the angulation of Winter: horizontal, mesioangular, vertical and distoangular. One can also see a greater relevance to the indication of prophylactic removal of male individuals aged over 35 years.